2019
DOI: 10.1016/j.jmoldx.2019.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Analytical Comparison of Methods for Extraction of Short Cell-Free DNA from Urine

Abstract: CME Accreditation Statement: This activity ("JMD 2019 CME Program in Molecular Diagnostics") has been planned and implemented in accordance with the accreditation requirements and policies of the Accreditation Council for Continuing Medical Education (ACCME) through the joint providership of the American Society for Clinical Pathology (ASCP) and the American Society for Investigative Pathology (ASIP). ASCP is accredited by the ACCME to provide continuing medical education for physicians. The ASCP designates th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
93
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(93 citation statements)
references
References 47 publications
0
93
0
Order By: Relevance
“…In addition, urinary cfDNA also reflects the systemic status of patients, as it is derived from both the urinary tract and the circulatory system [16]. However, although many studies have compared the various extraction methods of circulating cfDNA in blood [17][18][19], limited data are available on methods for urinary cfDNA extraction [20,21]. Most studies have been conducted on urinary DNA, regardless of being genomic DNA or cfDNA [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, urinary cfDNA also reflects the systemic status of patients, as it is derived from both the urinary tract and the circulatory system [16]. However, although many studies have compared the various extraction methods of circulating cfDNA in blood [17][18][19], limited data are available on methods for urinary cfDNA extraction [20,21]. Most studies have been conducted on urinary DNA, regardless of being genomic DNA or cfDNA [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted January 25, 2021. ; https://doi.org/10.1101/2021.01.19.21249296 doi: medRxiv preprint 21 binding of short cfDNA, but did not report its analytical performance (e.g., percent recovery) (8). While the Wizard method improves upon conventional silica-based methods, our past testing revealed limited recovery (<35%) of ≤150 bp fragments (31). It was also highly dependent on urine composition and is likely to fail in samples with high pH and/or low nontarget DNA concentrations (31) Past studies also enrolled few smear-negative participants, and thus have not tested the ability to detect urine cfDNA in individuals with paucibacillary TB who stand to benefit most from a non-sputum-based test.…”
Section: Discussionmentioning
confidence: 93%
“…While the Wizard method improves upon conventional silica-based methods, our past testing revealed limited recovery (<35%) of ≤150 bp fragments (31). It was also highly dependent on urine composition and is likely to fail in samples with high pH and/or low nontarget DNA concentrations (31) Past studies also enrolled few smear-negative participants, and thus have not tested the ability to detect urine cfDNA in individuals with paucibacillary TB who stand to benefit most from a non-sputum-based test. In particular, the most promising study by Cannas et al included only 5% (2/43) smear-negative participants.…”
Section: Discussionmentioning
confidence: 93%
“…Alternatively, colorimetric quantitation is used, and more sensitive in the sub‐µg range 21 . A different approach utilizes quantitative real‐time PCR for DNA quantification, of which the reproducibility is however dependent on the initial DNA extraction method chosen, as well as potential interference from non‐DNA components in the sample itself 12,22 …”
Section: Resultsmentioning
confidence: 99%
“…Especially for sfDNA, however, this does not recover the total amount. Investigations into the recovery of sfDNA from solid‐phase extraction kits have shown that for DNA fragments < 50 bp and < 100 bp, only about 16.5% and 27.7% (median across various extraction kits) are recovered, respectively 11‐13 …”
Section: Introductionmentioning
confidence: 99%